The role of teachers’ language proficiency in teaching English in the Transcarpathian Hungarian schools in Ukraine - Huszti Ilona; Густі Ілона („RIK-U”, 2017)
Abstract. The article examines the relationship between teachers’ English language proficiency and their ability to teach English in the Transcarpathian Hungarian context. The results suggest that the higher the language proficiency level of the teacher, the more successful they can be in the teaching process. Further investigations are needed to identify the teachers’ real level of English language proficiency.

Резюме. У статті розглядається взаємозв'язок між рівнем володіння англійською мовою вчителями та їх вмінням викладати англійську мову в школах з угорською мовою навчання на Закарпатті. Отримані результати свідчать про таке: чим вищий у вчителя рівень володіння мовою, тим успішнішим є навчання англійської мови в ході навчального процесу. Необхідні подальші дослідження з метою визначення фактичного рівня володіння вчителем англійською мовою.

Absztrakt. A cikk megvizsgálja a tanárok angol nyelvtudása és angol tanítási képességük közötti különbséget a kárpátaljai magyar kontextusban. Az eredmények azt sugallják, hogy minél magasabb a tanár nyelvtudásának szintje, annál sikeresebb lehet a tanítási folyamatban. További felmérésekre van szükség a tanárok valódi angol nyelvtudásszintjének megismeréséhez.
A tanárok nyelvtudásának szerepe az angol nyelvtanításban a kárpátaljai magyar iskolákban
Роль рівня володіння мовою вчителями при викладанні англійської мови в закарпатських школах з угорською мовою навчання в Україні
https://kmf.uz.ua/wp-content/uploads/2017/12/Acta2017_szines.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005708
Keywords: teachers’ language proficiency; teaching English; native and non-native English speaking teachers; Transcarpathian Hungarian educational institutions